Urgensi Pengaturan Kebijakan Protokoler Kepala Daerah dalam Rangka Mewujudkan Efektivitas Tugas-Tugas Protokoler Kepala Daerah Kabupaten Batang Provinsi Jawa Tengah - Novi Lupitasari; Endang Larasati Setianingsih; Ika Riswanti Putranti; Teuku Afrizal (Universitas Medan Area, 2023)
This article aims to provide an overview of the protocol function in providing regional leadership services. Setting the tone, following manners, and acting respectfully—as a sign of respect for one's position or position in the state, government, or society—are examples of actions related to maintaining order during state-sponsored events. The focus of this research also looks at the roles and tasks of the protocol in supporting the activities of regional leaders in Batang Regency. The protocol has the responsibility of ensuring that the leader's activities/events are facilitated by providing services directly related to the leader's activities. In practice, the protocol is a multifunctional task because it carries out tasks as a planner, including program plans to regulatory arrangements. This includes their duties and roles as guides, lobbyists, general assistants, managers and waiters serving dignitaries or guests. This study applies the concept of